Definition of "fairy circles" and how they differ from other common vegetation gaps and plant rings. (19th November 2021) - Getzin, Stephan; Yizhaq, Hezi; Tschinkel, Walter R.
Abstract: Aims: The fairy circles along the Namib Desert in southern Africa are round grassland gaps that have puzzled scientists for about 50 years. With the discovery of fairy circles in Australia in 2016, the debate on the origin of the circles has been extended to a new continent. Research interest on the topic has since then risen strongly but so has the use of the term "fairy circle". This term has become more imprecise and, by analogy, has been applied to circular vegetation gaps or plant rings that are largely unrelated to fairy circles. For this reason, we define the concept of fairy circles by identifying their three main characteristics based on in situ field observations and soil excavations to larger‐scale spatial patterns, and regional‐scale distribution. Results: Following this approach, fairy circles are defined by: (a) being "empty gaps" in grassland without a central insect‐nest structure; (b) their ability to form spatially periodic patterns, which are regular hexagonal patterns with an extraordinary degree of spatial ordering; and (c) their strongly regional distribution confined within a narrow arid climatic envelope. In these combined traits, fairy circles differ from other common vegetation gaps which, for example, always have a central insect‐nest structure and may occur across broad climatic gradients on continents. Also plant rings have their own specific characteristics that largely differ from the combined attributes of genuine fairy circles. Conclusions: There are many other vegetation‐gap patterns in arid lands but if such gaps cannot jointly show the three characteristics defining the fairy circles, they should be carefully discussed on their own, rather than mixing them up with fairy circles. Our synthesis provides a new etymology for the different types of vegetation gaps and rings, aiming to guide the reader through various classes of circular plant patterns. Abstract : The fairy circles of Namibia are one of nature's greatest mysteries. The term "fairy circles" was established in ecology more than 20 years ago, but recently has been used interchangeably for other circular patterns that are largely unrelated. Here we summarize the main characteristics of fairy circles and show how they differ from common vegetation gaps and plant rings.